An insertional point mutation inactivates NolR repressor in Rhizobium meliloti 1021. - Cren, M (1994)
In the majority of Rhizobium meliloti isolates, nod gene expression is controlled by NolR, but this is not the case in a few strains including the widely used laboratory strain 1021. In 1021, the lack of NolR function was shown to be due to a single insertional mutation in the C-terminal coding sequence which abolished the DNA-binding ability, though the helix-turn-helix motif remained intact. This indicates that the C-terminal part of the protein is also essential for DNA binding. We conclude that in this species, control of nod gene expression involves NolR and strain 1021 represents an exception in which the NolR function was lost by a single event.